Evaluasi Karakteristik Fisik dan Uji Iritasi Akut Dermal Sediaan Losion yang Mengandung Senyawa (E)–1–(2–Hidroksifenil)–3–(4–Metoksifenil)prop–2–en–1–on - nesa agistia; Ferdy Firmansyah; Ihsan Ikhtiarudin; Selvi Rahmawati (LPPM Universitas Abdurrab, 2026)
Chalcones are secondary metabolites belonging to the flavonoid class that exhibit sunscreen activity. The chalcone analog (E)-1-(2-hydroxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one has the potential to be developed as an active ingredient in sunscreen formulations. In this study, the compound was formulated into an oil-in-water (O/W) lotion at three different active ingredient concentrations, namely F1 (0.1%), F2 (0.3%), and F3 (0.5%). The formulations were subsequently evaluated for their physical properties and acute dermal irritation in vivo using experimental animals. The physical evaluation demonstrated that all lotion formulations were homogeneous, had a pH of 6.90, exhibited an oil-in-water emulsion type, possessed a viscosity of 8,866 cps, showed pseudoplastic thixotropic flow behavior, and had a spreadability of 6.25 cm. Furthermore, no significant changes in the physical properties were observed after 8 weeks of storage. The acute dermal irritation test revealed that all formulations had an irritation index of 0, indicating a very slight irritation response. These findings demonstrate that all lotion formulations met the required quality criteria for lotion preparations and were well tolerated, supporting their potential as safe topical sunscreen formulations.